Mitochondrial Tethers and Their Impact on Lifespan in Budding Yeast - Pernice, Wolfgang M.; Swayne, Theresa C.; Boldogh, Istvan R.; Pon, Liza A. (Frontiers in Cell and Developmental Biology, 2018)
Tethers that link mitochondria to other organelles are critical for lipid and calcium transport as well as mitochondrial genome replication and fission of the organelle. Here, we review recent advances in the characterization of interorganellar mitochondrial tethers in the budding yeast, Saccharomyces cerevisiae. We specifically focus on evidence for a role for mitochondrial tethers that anchor mitochondria to specific regions within yeast cells. These tethering events contribute to two processes that are critical for normal replicative lifespan: inheritance of fitter mitochondria by daughter cells, and retention of a small pool of higher-functioning mitochondria in mother cells. Since asymmetric inheritance of mitochondria also occurs in human mammary stem-like cells, it is possible that mechanisms underlying mitochondrial segregation in yeast also operate in other cell types.